Is colorectal cancer associated with altered bowel habits in young patients?. Issue 5 (28th December 2020) - Rajagopalan, Ashray; Antoniou, Ellathios; Morkos, Marina; Rajagopalan, Ellen; Arachchi, Asiri; Chouhan, Hanumant; Nguyen, Thang Chien; Teoh, William
Abstract: Background: There is a rising incidence in young‐onset colorectal cancer, with these patients falling outside of routine screening programmes. The aim of the study is to characterize the nature of altered bowel habits in young patients who are diagnosed with colorectal cancer. Methods: A retrospective audit was conducted of adult patients younger than 45 years admitted under a Colorectal Surgery unit (Dandenong Hospital, Victoria) from 2011 to 2019 for the resection of colorectal cancer. We compared the patients' self‐characterization of their bowel habits (from the medical record) with clinical and pathological data. Results: A total of 75 patients were identified, aged between 18 and 45 years, who had surgical resection of colonic or rectal adenocarcinoma between 2011 and 2019. Forty‐two (56%) presented with altered bowel habit (irregular bowel habit n = 13, 17%; constipation n = 13, 17%; diarrhoea n = 23, 31%). Constipation approached significance in association with left‐sided colonic cancer. Fatigue approached significance in association with right‐sided colonic cancers, which were less likely to present with bleeding or constipation, and approached significance in being less likely to present with diarrhoea. Rectal cancers were more likely to present with bleeding. Conclusion: Constipation was associated with left‐sided colonic cancers, while right‐sided colonic cancers were less likely to present with either constipation or diarrhoea. Our findings reinforce the need for clinicians to consider colorectal cancer as a differential diagnosis in young patients with altered bowel habits, or in patients with fatigue in the absence of specific bowel symptoms. Further prospective research is needed to further define bowel habits in this cohort. Abstract : We describe patterns of bowel habits in young patients diagnosed with colorectal cancer. There was a range of bowel habits captured including irregular bowel habit, constipation and diarrhoea. Constipation was associated with left‐sided colonic cancers, while right‐sided colonic cancers were less likely to present with either constipation or diarrhoea.